Crossing Arizona [videorecording (DVD)] - Mathew, Joseph, 1965-; DeVivo, Dan (Passion River Films, 2008)
With Americans on all sides of the issue up in arms and Congress embroiled in a knock-down-drag-out policy battle over how to move forward, this videodisc shows how we got to were we are today, heightened security in California and Texas has pushed illegal border-crossers into the Arizona desert.